The effect of gymball use on pain intensity during the active phase of the first stage of labor among women - Zakiyya Tunnisa; Meinasari Kurnia Dewi; Magdalena Tri Putri (THE JOURNAL OF Mother and Child Health Concerns, 2025)
Background: Labor pain arises from uterine muscle stretching, which can affect overall physiological functions, including increased oxygen demand, elevated respiratory rate, higher blood pressure, and disturbances in the digestive system. The intensity of pain experienced may also influence the mother’s preference for a delivery method. Therefore, effective pain management during labor is essential for maternal comfort and safety. Purpose: To analyze the effect of gym ball use on pain intensity during the active phase of the first stage of labor among women delivering at PMB Ny. T, Ciherang Village, Cianjur Regency, in 2025. Method: A quasi-experimental design with a one-group pretest–posttest approach was employed. The sample consisted of 30 mothers in the active phase of the first stage of labor who experienced labor pain. Purposive sampling was used, and data were collected through observational sheets. Results: Before the intervention, the majority of respondents experienced very severe labor pain (24 mothers; 80%). After the gym ball intervention, most respondents reported moderate pain intensity (22 mothers; 73.3%). The statistical analysis yielded a p-value of 0.000 (p < 0.05), indicating that H₀ was rejected and Hₐ was accepted, thereby confirming a significant effect of gym ball use on pain intensity during the active phase of the first stage of labor. Conclusion: Gym ball use significantly reduces pain intensity among mothers in the active phase of the first stage of labor. Suggestion: Mothers preparing for childbirth are encouraged to understand and utilize gym balls as a non-pharmacological method to reduce labor pain